Two-dimensional Analysis of Cracks Propagation in Structures of Concrete - Benarbia, D.; Benguediab, M.; Benguediab, S. (Engineering, Technology & Applied Science Research, 2013)
In this article we present a numerical simulation that allows describing and studying the damage of concrete works subjected to various stress types. In this study, the propagation of cracks in the concrete is analyzed as of their appearance, which requires having a thorough knowledge of the mechanical behavior of the material. The mechanical approach which leads to better understanding of fracture phenomena and can give satisfactory results, is that of the elastic linear mechanics of failure. The interest in this study is focused in the development processes of the cracks from a phenomenological point of view. The analysis is carried out by using fracture criteria while being based on the determination of the critical stress intensity factors, for each case of the several elaborate tests of indirect tensile per bending and Brazilian Disc. The analysis is carried out in a two-dimensional medium by the finite element method by using the ABAQUS software. The results obtained are compared with experimental data obtained analytically from other authors.